Independent Evaluation of a Commercial AI Software for Incidental Findings of Pulmonary Embolism (IPE) on a Large Hospital Retrospective Dataset - S. Ambrogio; I. Verdon; B. Laureano; K. V. Ramnarine; F. Fedele; D. Vilic; I. Honey; E. Barton; C. Goncalves; Sze Mun Mak; H. Shuaib; A. Jacques (Radiology Research and Practice)
Conclusions: The AI software detected IPE with a high diagnostic accuracy on a large NHS dataset, showing that AI–supported reporting could improve diagnostic accuracy and reduce times to diagnosis.